Mental health of medical personnel during the COVID‐19 pandemic - Jovana Antonijevic (Brain and Behavior, 2020)
Abstract Introduction The coronavirus disease 2019 (COVID‐19) pandemic caused significant changes in the everyday functioning of the general population, as well as medical workers. Medical personnel, especially those in direct contact with COVID‐19 patients, could have increased levels of stress, anxiety, and depression. The objective of this study was to explore the mental health status of medical personnel in Serbia during the pandemic by assessing stress levels, symptoms of anxiety, and depression. Methods This cross‐sectional study was conducted as an online‐based survey, in the period from 8 April to 14 April 2020, during the COVID‐19 pandemic. The study included 1678 participants, and the snowball sampling technique was used to reach healthcare professionals. The level of stress and symptoms of depression and anxiety were assessed among medical personnel in Serbia by the 10‐item Perceived Stress Scale (PSS), the Beck Depression Inventory IA (BDI‐IA), and the 7‐item Generalized Anxiety Disorder Scale (GAD‐7), respectively. Results A total of 1678 participants completed the survey, with a mean age of 40.38 ± 10.32 years, of which 1,315 (78.4%) were women, and 363 (21.6%) were men. Out of these, 684 (40.8%) participants were medical personnel, and 994 (59.2%) were people of other professions. Frontline medical personnel reported higher scores on all measurement tools than second‐line medical personnel (e.g., mean PSS scores: 19.12 ± 5.66 versus 17.53 ± 5.71; p = .006; mean GAD‐7 scores: 8.57 ± 6.26 versus 6.73 ± 5.76; p = .001; mean BDI‐IA scores: 9.25 ± 8.26 versus 7.36 ± 7.28; p = .006). Binary logistic regression showed that the probability of developing more severe anxiety symptoms doubles in frontline medical personnel. Conclusion Our findings suggest that frontline medical personnel is under an increased psychological burden during the COVID‐19 pandemic, having higher levels of stress, anxiety, and depression than second‐line medical personnel. Adequate measures should be taken to relieve this burden and preserve the mental health of frontline medical personnel.